THE EFFECT OF SELF-EQUILIBRATING STRESSES ON THE NATURAL FREQUENCIES OF ELASTICALLY RESTRAINED RECTANGULAR PLATE (Journal of Engineering, 2005)
An investigation has been made into the effect of residual stresses on the vibration, characteristics of thin rectangular plates clastically restrained against rotation along three edges and free on the fourth edge .General frequency equation with and without including the effect of residual stresses has been obtained. Exact frequency expressions including the eflect of residual stresses for the cascs: S-S-S-F,S-S-C-F.C-C-S-F.C-S-S-F. C-S-C-F.C-C-C-F were also obtained. The eflect of the position of welding along the width of the plate for all cases was also included. Actual plate models were testea and the results were compared with the theoretical predictions giving good agreement